HUBUNGAN RESPONSE TIME PERAWAT DENGAN TINGKAT KECEMASAN KELUARGA PASIEN KATEGORI TRIAGE KUNING DI IGD RUMAH SAKIT DAERAH BALUNG: Relationship between Nurse Response Time and Family Anxiety Level of Yellow Triage Category Patients in the Emergency Room of Balung Regional Hospital - Kurniawan, Muhammad Abdul Rohman; Susilo, Cipto; Hamid, Mohammad Ali (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
An emergency is a clinical situation that requires immediate medical intervention to save lives and prevent disability. There are many complaints filed by families of patients who feel they do not get service even though they come early, this is due to several factors including internal factors and external factors. The length of service in the emergency room causes the patient's family to be anxious because they do not immediately get treatment. The purpose of this study was to determine the relationship between the nurse's response time and the anxiety level of the family of patients in the yellow triage category in the emergency room of Balung Regional Hospital. This research design is a correlation with a crosssectional approach. The population of this study was 701 respondents with a sample of 70 respondents. The sampling technique used was non probability sampling with purposive sampling approach. The instruments in this study were questionnaires and observation sheets. The results of the Spearman's Rho statistical test with α = 0.05 obtained p value = 0.001 and r = 0.401 which means that response time has a moderate relationship with the patient's family anxiety level. The conclusion is that there is a relationship between response time and the anxiety level of the family of patients in the yellow triage category at the Emergency Room of Balung Regional Hospital.